An investigation on residual strength and failure probability prediction for plain weave composite under random fatigue loading. (March 2019) - Chen, Xiaojie; Sun, Yi; Wu, Zengwen; Yao, Liaojun; Zhang, Yuli; Zhou, Song; Liu, Yizhi
Highlights: A new model is proposed to predict the residual strength. The difference in modulus is taken into account. A conditional PDF of Rayleigh distribution is adopted. The failure probability is applied to describe the damage. Abstract: The residual strength and the failure probability of the plain weave carbon-fiber reinforced epoxy composite subjected to random fatigue loading are investigated. According to the constant amplitude residual model and the experimental S-N curves, a new model is proposed, in which both the probability density function of stress peaks and the power spectrum density of stochastic processes are employed. The degradation of residual strength ( dSr ) in a time increment ( dt ) is calculated via an integration of the decrease of residual strength due to the stress peaks ( dSr p ) in the definitional domain of the peak probability density function. A linear damage accumulation of residual strength is used in this time increment. The evolutions of the residual strength with time are determined via a double integral method. The new model's prediction results are in good agreement with the experiment results and it can give the curves of the variation of fatigue life with failure probability.